Clinical and biochemical assessment of the effect of topical use of coenzyme Q10 versus topical corticosteroid in management of symptomatic oral lichen planus: randomized controlled clinical trial - Mostafa Abdelsamie; Fat'heya Zahran; Amal A. Hussine; Olfat Shaker; Abdulaziz Mohsen Al-mahallawi (BMC, 2023)
Abstract Background Oral lichen planus (OLP) is a chronic mucocutaneous immunologically mediated condition that has a great adverse effect on oral functions. Corticosteroids are still the first drugs of choice used in the treatment of OLP; however, they have extensive medical side effects. The present study was carried out to assess the clinical therapeutic effect of the topical use of coenzyme Q10 (coQ10 or ubiquinol) versus topical corticosteroids in the management of symptomatic OLP and to determine whether the effect, if any, was due to the powerful antioxidant activity of coQ10. Subjects and methods We performed a randomized, double blinded controlled trial at the Faculty of Dentistry, Cairo University, Egypt. The study was conducted on 34 patients suffering from symptomatic OLP. Patients were randomly divided into two groups: intervention group (I),who received topical CoQ10 in the form of mucoadhesive tablets (40% CoQ10) 3 times daily for one month and control group (II),who received topical corticosteroid (kenacort in Orabase: triamcinolone acetonide 0.1% 5-g adhesive paste - dermapharm), 4 times daily for one month. Patients were evaluated at one-week intervals using the clinical parameters (score) of pain (VAS) and lesion size. Additionally, salivary levels of malondialdehyde (MDA) were detected in both groups before and after treatment using ELISA. All recorded data were analysed using independent t test, ANOVA followed by Bonferroni post hoc test for lesion size and salivary level of MDA data and Mann-Whitney U test and Friedman test for VAS data. Results Both groups showed a significant reduction in pain and the size of the lesions (p ≤ 0.05) with no statistically significant difference between them (p > 0.05), and this clinical improvement was associated with a reduction in the salivary levels of MDA in both groups. Conclusions The topical use of CoQ10 mucoadhesive tablets was as effective as the topical use of triamcinolone acetonide, and its clinical effect was associated with a reduction in the salivary level of MDA. Trial registration The study protocol was registered at www.clinicaltrial.gov (NCT04091698) and registration date: 17/9/2019.